Systematic Literature Review tentang Implementasi Pembelajaran Mitigasi Bencana di Mata Pelajaran IPS Sekolah Dasar - Nurhalizah Apriyani; Siti Nur Aprilianti; Tria Nur Erliani Agustin; Yona Wahyuningsih (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Indonesia is highly vulnerable to natural disasters due to its position along the Pacific Ring of Fire and its complex geographical landscape. This condition underscores the importance of introducing disaster mitigation education from the elementary school level. Social Studies serves as a strategic subject for cultivating students’ environmental awareness, social responsibility, and disaster preparedness. This study conducts a Systematic Literature Review (SLR) to examine how disaster mitigation has been integrated into Social Studies learning in Indonesian elementary schools. Following PRISMA procedures and Kitchenham’s methodological framework, relevant studies published between 2020 and 2025 were identified and thematically analyzed. The review reveals that contextual, experiential, and realistic learning approaches such as simulations and field observations are most frequently implemented. The use of visual and digital media, including comics, digital booklets, and animated videos, effectively enhances students’ understanding, motivation, and preparedness. Despite these positive outcomes, challenges remain in terms of limited facilities and teacher readiness. The study recommends continuous teacher professional development and the systematic inclusion of disaster mitigation within the Social Studies curriculum.